2022
DOI: 10.3390/nano12203621
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical Properties of Vegetable Oil-Based Hybrid Nanofluids Containing Al2O3-TiO2 Nanoparticles as Insulation Oil for Power Transformers

Abstract: The massive demand in the electrical power sector has resulted in a large demand for reliable, cost efficient, and environmentally friendly insulation oil to reduce the dependency on mineral oil. The hybridization of nanoparticles in vegetable oil is a novel method to enhance the thermal properties of vegetable oil. This study focuses on the experimental investigation of the thermophysical properties of coconut oil, soybean oil, and palm oil-based hybrid nanofluids suspended with Al2O3-TiO2 nanoparticles at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Therefore, these results signify that the higher the mass fraction of nanoparticles addition to the base oil increases the density. In this density test, CaCO 3 nanoparticles have a role in changing fluid properties, where the addition of CaCO 3 nanoparticles to the base fluid can increase the density of the cutting fluid sample, it is because the CaCO3 nanoparticles mixed can increase the amount of substances contained in a unit volume of base fluid [66].…”
Section: Densitymentioning
confidence: 99%
“…Therefore, these results signify that the higher the mass fraction of nanoparticles addition to the base oil increases the density. In this density test, CaCO 3 nanoparticles have a role in changing fluid properties, where the addition of CaCO 3 nanoparticles to the base fluid can increase the density of the cutting fluid sample, it is because the CaCO3 nanoparticles mixed can increase the amount of substances contained in a unit volume of base fluid [66].…”
Section: Densitymentioning
confidence: 99%
“…These insulating liquids are derived from both seeds and flowers. VOs are the subject of several studies in an effort to use them as insulating oils in transformers and create eco-friendly environments [3]. VOs are thought to be more nature-friendly liquids due to their high biodegradability (>95 %), high flash and fire points (both >300 °C), and lesser flammability [4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a comparative study presenting the effect of each NP with different types of base fluids is not presented and the effect of the thermophysical properties of these oils on the electrical consumption of the pump is not also evaluated in the previous studies. A thermophysical evaluation of three types of vegetable oils including coconut, soybean and palm oil suspended with hybrid nanoparticles was carried out by Vignesh et al [ 28 ]; Among these fluids, palm oil-based NFs were found to have better thermophysical properties. However, a study over an annual period and not just a daily period of these nanofluids based on vegetable oils could be very conclusive.…”
Section: Introductionmentioning
confidence: 99%